Relevance of the irrigation and soil management system to optimize maize crop production under semiarid Mediterranean conditions - Samuel Franco-Luesma; José Cavero; Jorge Álvaro-Fuentes (Agricultural Water Management)
Irrigation system and soil management through the different tillage system may have a significant impact on maize crop performance due to their capabilities to modify soil water content and soil physical and biochemical properties. Over the current climate change scenarios, the evaluation and implementation of agricultural systems that increase the efficiency in the use of the resources, like water or soil fertility, must be a priority. The aim of this study was to evaluate the impact of two well differentiated irrigation systems (i.e. sprinkler irrigation, S, flood irrigation, F) and three different tillage system (i.e. conventional tillage, CT, no-tillage maintaining the crop stover, NTr, no-tillage removing the crop stover, NT) on maize growth and yield % and agronomic efficiency of nitrogen (AEN) and irrigation water productivity (WPI) for a four years maize monoculture under semiarid Mediterranean conditions. On average, S irrigation increased maize grain yields by 16 % and AEN and WPI by 23 and 33 %, respectively, compared to F irrigation system (with an average total irrigation water applied that was 25 % lower under S irrigation system). The tillage system showed the greatest differences when was implemented under F irrigation, showing CT better crop performance than NT. Under S irrigation, the tillage system had lower o non-impact on yield components, observing similar yield, AEN and WPI between CT and NTr and NT tillage systems. This work highlighted that the adoption of water saving irrigation system (like S irrigation), together with the implementation of more conservative tillage practices, such as no-tillage, is a win-win strategy to maintain the sustainability the high-yielding maize system under semiarid Mediterranean conditions.